Menelaah Makna Kebebasan Individual Berhadapan dengan Protokol Kesehatan Covid 19 - Antonis Baju Nujartanto (Sekolah Tinggi Filsafat Seminari Pineleng, 2021)
One of the recommended solutions to reduce the spread of the Covid-19 outbreak is the implementation of health protocols, such as washing hands, wearing masks, maintaining social distance, staying away from crowds, and reducing mobility. However, the implementation of health protocols has raised philosophical questions on the meaning of personal freedom. Do health protocols limit or even hinder a person's freedom? This paper aims to look at the meaning of personal freedom in dealing with health protocols during the Covid-19 pandemic. Based on literature studies, the author tries to redefine individual freedom in the context of dealing with a pandemic. Personal freedom is placed in the context of the spirit and efforts to tackle the problems of this pandemic together.